Diabetic foot as a complication of diabetes - Patrycja Ręba (Kazimierz Wielki University, 2020)
Admission Diabetic foot is a chronic complication of diabetes. Is a shallow or deep skin ulcer. It can occur with both type 1 and type 2 diabetes. Diabetic foot can appear in anyone with diabetes. This condition is associated with all kinds of complications or pathological changes that are a direct result of diabetes. Patients also complain of ulcers, infections and neurogenic arthropathy also known as Charcot's joints.   Aim  The aim of the study is to analyze the diabetic foot as a complication of diabetes. Material and method  Review of available literature on the subject. Results Along with the diagnosis of diabetic foot, doctors classify the disease according to the Wagner classification, i.e. a 6-point scale. The division of the diabetic foot syndrome takes into account the assessment of blood supply, the size and penetration of the ulcer, as well as the severity of the infection and the occurrence of diabetic neuropathy. The first grade of diabetic foot syndrome is free of signs and symptoms of infection, as there is no infection. In the second degree, the infection is local and covers only the skin and subcutaneous tissue, without involvement of deeper tissues and without systemic symptoms. In the third degree of diabetic foot syndrome, a local infection is present without involvement of deeper tissues with erythema over 2 cm in diameter.fascia. The fourth degree of diabetic foot syndrome is characterizedsevere infection, including local lesions in combination with systemic symptoms. Conclusions Diabetic foot is treated primarily by leveling diabetes and maintaining normal glycemia. In the case of large ulcers, a visit to a surgeon will be required who will develop the ulcer and recommend further action. Also, if you get an infection you will need to take by mouthantibiotic therapy or appropriate topical preparations. Diabetic foot syndrome is just one of many complications of untreated diabetes that can lead to disability or even premature death. This should be a cautionary tale for people who disregard the need for systematic blood glucose control.